Comparing data quality of fertility and first sexual intercourse histories. - Wu, Lawrence L.; Martin, Steven P.; Long, Daniel A. (Journal of Human Resources)
This paper evaluates the data quality of two demographic variables in light of hypotheses on respondent recall from the literature on survey methodology. An emerging consensus in this literature is that recall of the timing of an event declines with recall duration unless the dating of an event is frequently “rehearsed.” We provide empirical evidence consistent with this hypothesis by assessing the quality of demographic data on two event history variables as supplied by female respondents. A first outcome concerns the interval between a first and second birth. We assess examine birth intervals using birth registration data from the Vital Statistics on Natality (VSN) and individual-level survey data from the 1990 June Current Population Survey (CPS), the 1979-93 waves of the National Longitudinal Survey of Youth (NLSY), and the 1988 National Survey of Family Growth (NSFG). Overall, we find relatively little variation in the quality of birth interval data across these four surveys, with one exception—CPS data in which responses have been allocated. A second demographic variable is age at first sexual intercourse. We engage in several analyses of this variable. First, we use NLSY data to analyze discrepancies between successive reports on age (to the nearest year) at first intercourse. Second, we analyze a form of partially missing data (respondent inability to recall the calendar month of intercourse) that occurs in both the NLSY and NSFG. Third, we identify NLSY respondents who, in successive interviews, give contradictory reports about whether or not sexual activity had been initiated. Our findings suggest that data quality varies significantly with duration of recall and with measures of respondent ability related to arithmetic facility and memory. Observed differences by race and ethnicity narrow substantially when controlling for these and other background factors. We find evidence for a nonlinear association between duration of recall and data quality, with similar patterns occurring in both the NLSY and NSFG. Finally, our NLSY results are suggestive of a pattern in which recent initiation of sexual activity may be concealed by respondents. Reprinted by permission of the publisher.